Answer

Verified

339.9k+ views

**Hint:**Here, a trigonometric equation is given which we have to simplify.

Here, we are using a basic formula for simplifying the equation i.e. ${{\left( a+b \right)}^{2}}={{a}^{2}}+2ab+{{b}^{2}}$

We also have to use a trigonometric functions of ${{\sin }^{2}}x+{{\cos }^{2}}x=1$

And after solving the equation, we will get the value of $x$ in the form of angles and convert it into radians. We can check the value of $x$ by substituting the value of $x$ in the given equation.

**Complete step by step solution:**

In this numerical a trigonometric equation is given which is as follows:

$\sin x+3\cos x=3...(i)$

Squaring the equation $(i)$ for getting some identities to solve further.

${{\left( \sin x+3\cos x \right)}^{2}}={{\left( 3 \right)}^{2}}$

Now, simplify the above equation. The left hand side is in the form of ${{\left( a+b \right)}^{2}}={{a}^{2}}+2ab+{{b}^{2}}$

${{\sin }^{2}}x+2\times 3\sin x\cos x+{{\left( 3 \right)}^{2}}{{\cos }^{2}}x=9$

$\Rightarrow {{\sin }^{2}}x+6\sin x\cos x+9{{\cos }^{2}}x=9$

Now transpose $9{{\cos }^{2}}x$ to the right side ${{\sin }^{2}}x+6\sin \cos x=9-9{{\cos }^{2}}x$

${{\sin }^{2}}x+6\sin x\cos x=9\left( 1-{{\cos }^{2}}x \right)$

As, we know that,

${{\sin }^{2}}x+{{\cos }^{2}}x=1$

$\Rightarrow {{\sin }^{2}}x=1-{{\cos }^{2}}x$

$\Rightarrow {{\sin }^{2}}x+6\sin x\cos x=9{{\sin }^{2}}x$

Subtract ${{\sin }^{2}}x$ on the both sides from the above equation. We get,

${{\sin }^{2}}x+6\sin x\cos x-{{\sin }^{2}}x=9{{\sin }^{2}}x-{{\sin }^{2}}x$

$6\sin x\cos x=8{{\sin }^{2}}x$

Now separate the like terms,

$\dfrac{\sin x\cos x}{{{\sin }^{2}}x}=\dfrac{8}{6}$

$\Rightarrow \dfrac{\cos x}{\sin x}=\dfrac{8}{6}$

$\Rightarrow \cot x=\dfrac{4}{3}$

We know that,

$\cot x=\dfrac{1}{\tan x}={{\tan }^{-1}}x$

$\Rightarrow x={{\tan }^{-1}}\left( \dfrac{3}{4} \right)...(ii)$

$\Rightarrow x=36.80$

$x=0.6435$ radians

**Therefore the value of $x$ for the given trigonometric equation is $0.6435$ radians.**

**Additional Information:**

For solving a trigonometric equation we have to transform that trigonometric equation into one or more than one basic trigonometric function or equations.

It means that solving a trigonometric equation is nothing but solving one or more basic trigonometric equations or functions.

Trigonometric equations or functions.

Trigonometric equations has $4$ basic equations or functions:

$\sin x=a,\cos x=a$

$\tan x=a,\cot x=a$

Using above basic functions of trigonometry other simplified equations can be make.

**Note:**In equation $(ii)$

$x={{\tan }^{-1}}\left( \dfrac{3}{4} \right)$

But the original equation is,

$\cot x=\dfrac{4}{3}$

$\Rightarrow\dfrac{1}{\tan x}=\cot x$

${{\tan }^{-1}}x=\cot x$

Now, ${{\tan }^{-1}}\left( \dfrac{3}{4} \right)$

$x={{\tan }^{-1}}\left( \dfrac{3}{4} \right)$

$=0.6435$ radians

We can solve this questions in other way too which is as follows:

The given equation is,

$\sin x+3\cos x=3...(i)$

Now, put $\tan a=3$

$a={{\tan }^{-1}}\left( 3 \right)$

$a=71.56$

And $\cos a=\cos \left( 71.56 \right)=0.32$

Now, put $\dfrac{\sin a}{\cos a}$ at the place of $3$ in left side only of the equation $(iii)$

$\left( \dfrac{\sin a}{\cos a} \right)\cos x=3...(ii)$

Multiply $\cos a$ at both sides of equation $(ii)$

$\sin x\cos a+\left( \dfrac{\sin a}{\cos a} \right)\cos a\cos x=3\cos a$

$\Rightarrow\sin x\cos a+\sin a\cos x=3\cos a$

$\Rightarrow\sin \left( x+a \right)=3\cos a...(iii)$

But as we already calculated above

$a=71.56$

$\cos a=0.32$

The equation $(iii)$ becomes

$\sin \left( x+71.56 \right)=3\left( 0.32 \right)$

$\Rightarrow\sin \left( x+71.56 \right)=0.96$

The angle should be of $180{}^\circ $

$x+71.56{}^\circ =0$

$\Rightarrow x+71.56{}^\circ =180{}^\circ -71.56{}^\circ $

$\Rightarrow=108{}^\circ .44{}^\circ $

$x=108{}^\circ .44{}^\circ -71.56{}^\circ $$x=36.88{}^\circ $

We can also verify the answer.

Put value of $x=36.86{}^\circ $ or $x=0.6435$ in equation $(i)$

$\sin x+3\cos x=3$

$\Rightarrow\sin \left( 36.86 \right)+3\cos \left( 36.86 \right)=3$

$\Rightarrow0.6+3\times 0.8=3$

$\Rightarrow0.6+2.4=3$

$3=3$

Or $\sin x+3\cos x=3$

$\sin \left( 0.6435 \right)+3\cos \left( 0.6435 \right)=3$

$\Rightarrow0.012+3\times 2.9997=3$

$\Rightarrow3.0109=3$

$3\simeq 3$

From above it is clear that the value of $x=36.86{}^\circ $ or $x=0.6435$ radians is correct.

Recently Updated Pages

Basicity of sulphurous acid and sulphuric acid are

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

What is the stopping potential when the metal with class 12 physics JEE_Main

The momentum of a photon is 2 times 10 16gm cmsec Its class 12 physics JEE_Main

Using the following information to help you answer class 12 chemistry CBSE

Why should electric field lines never cross each other class 12 physics CBSE

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Describe the poetic devices used in the poem Aunt Jennifers class 12 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

Change the following sentences into negative and interrogative class 10 english CBSE

State the laws of reflection of light

State and prove Bernoullis theorem class 11 physics CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE